PENGARUH PENERAPAN METODE KOOPERATIF MODEL JIGSAW PADA PEMBELAJARAN PPKN TERHADAP PENINGKATAN HASIL BELAJAR SISWA SD - Intan Nur Syafitri; Sabina Khoerussahra; Khoirina Irawan Putri; Muhamad Febrian; Zainab Nabila Saputri; Oktavia Devi Ramadhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cooperative learning is an approach that emphasizes cooperation among students in achieving learning objectives. This approach is considered effective because it can increase student engagement, interaction between students, and understanding of learning materials. In cooperative learning, the Jigsaw method is often applied, namely a group-based learning method in which students are divided into home groups and expert groups, then share knowledge with their group members. This method encourages students to be active, responsible, and able to develop social and communication skills. This study aims to analyze the effectiveness of the Jigsaw method on student learning outcomes in the subject of Citizenship Education (PPKN), and to understand the method's influence on student understanding and engagement in the learning process. This study uses a qualitative approach with a literature study method. Data were obtained through the collection and analysis of various relevant sources, such as scientific journal articles and the results of previous studies that discuss the application of the Jigsaw method in PPKN learning. The results of the analysis indicate that the Jigsaw method has a positive effect on improving student learning outcomes. In addition, this method is able to increase activeness, cooperation, and a deeper understanding of the concept of citizenship. The application of the Jigsaw method can contribute to developing democratic attitudes, a sense of responsibility, and critical thinking skills in students, which aligns with the learning objectives of Civics Education. Through discussion and reciprocal teaching between students, the learning process becomes more meaningful and student-centered. Therefore, the Jigsaw method can be used as an effective alternative learning model to improve the quality of Civics Education in schools.